BANKS' LOAN PORTFOLIO QUALITY MANAGEMENT (World Economics and Finance Bulletin, 2022)
In this article, theoretical views on the credit portfolio of commercial banks, methods of increasing the efficiency of managing the quality of the credit portfolio of commercial banks, analysis of quality management methods and thus the development of the lending system are studied